The Series of the Dialogue Character in Quran | سلسلة الشخصيات الحوارية في القرآن - Nabil Nabil (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
This article examines the character of angels and demons in the Qur'an. Angels and demons are two different human beings. angels are created from light. Demon were created from fire. al quran lot of communicating both in the form of a conversation. This study is the literature, the author chekcs some verses on Quran about this topic. This study proves that angels and demons are real although not viewable